Stalin's Man in Canada: Fred Rose and Soviet Espionage - Kealey, Gregory S. (Labour / Le Travail, 2013)
The article reviews the book, "Stalin's Man in Canada: Fred Rose and Soviet Espionage," by David Levy.
Keywords: Canada; Espionage; LEVY, David; Nonfiction; ROSE, Fred; STALIN'S Man in Canada: Fred Rose & Soviet Espionage (Book)